Swallowing function management in patients with disorders of consciousness: a scoping review - Long, Hua; Lu, Bixia; Tan, Qiao; Dai, Dongmei; Zeng, Fengfei (Frontiers in Neuroscience, 2025)
ObjectivePatients with disorders of consciousness often have concurrent swallowing difficulties, although the assessment methods, interventions, and their effectiveness have not been systematically described. This study aims to conduct a comprehensive review of assessment methods and rehabilitation interventions for swallowing function in patients with disorders of consciousness.MethodsThis scoping review was performed and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guideline. Studies that describe a screening method to examine swallowing function or assess a kind of swallowing management intervention among individuals with disorders of consciousness (DoC) were included. Following Arksey and O’Malley’s five-stage framework, databases including CNKI, WangFan, VIP, SinoMed, PubMed, Web of Science, Embase, ClinicalTrials.gov, Cochrane, Scopus, and Medline were systematically searched, from the inception of each database to June 2024. Relevant studies were extracted and analyzed. The main review question is “What has been studied about swallowing function management in patients with DoC?”.ResultsAssessment methods for swallowing function in patients with disorders of consciousness primarily included clinical swallowing assessments, scale-based evaluations, and instrument-based assessments. Rehabilitation interventions for swallowing function encompassed sensory stimulation, K-point stimulation, functional oral intake therapy, oral intermittent tube feeding, neuromuscular electrical stimulation, and acupuncture therapy. Most of the included studies did not explicitly specify the timing of swallowing assessment and intervention.ConclusionA standardized approach for evaluating and intervening in swallowing function among patients with disorders of consciousness is notably lacking. Selecting appropriate swallowing assessment tools and devising evidence-based management plans tailored to assessment results could improve the swallowing function and patient outcomes. More high-quality designing research that compares the assessment accuracy of different evaluation methods, as well as develops personalized interventions are imperative.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/SURBY.